Semi-deciduous forests syntaxa from Sierra Maestra, Eastern Cuba - Reyes, Orlando J.; Acosta, Félix (Lazaroa, 2014)
Five associations from two classis, three orders and four alliances are described in low Sierra Maestra semideciduous forests. Two of microphill semideciduous forests are in soils from calcareous rocks, while the three from mesophill semideciduos forests grow up in soils developed over volcanic rocks from El Cobre group. In this work we have used the Zurich – Montpellier school methodology, which is easily used in the Cuban archipelago.